Pengelolaan Warisan Budaya di Era Desentralisasi : Studi Komparatif Indonesia dengan Beberapa Negara - -, Muhammad Emir Al-Azkiya; Arni Fazira; Drajat Tri Kartono (Universitas Serang Raya, 2024)
Decentralization grants more authority to local governments in Indonesia to manage their affair, including cultural matters. This research aims to understand cultural decentralization in Indonesia and several foreign countries such as Turkey, Serbia, Jordan, Ukraine, and the Czech Republic in terms of managing and developing cultural heritage. This study employs a qualitative research approach with a library research method. Ten (10) articles indexed in Sinta 1-4 and Scopus were selected for analysis in this research. The findings of this study indicate that cultural decentralization in Indonesia and foreign countries, particularly Ukraine, shame similarities, and city branding by highlighting cultural heritage can positively impact economic progress through tourism and increase public awareness of preserving cultural heritage. Additionally, the role of local governments is crucial in determining the success of cultural decentralization in managing cultural heritage in Indonesia, Turkey, and Serbia. In contrast, the comparison of cultural decentralization in Jordan and the Czech Republic shows that centralization remains strong, even though local governments have the authority to manage their regions. Unlike Indonesia, decentralization is not merely a discourse. Keywords: Cultural Decentralization, Cultural Heritage, Indonesia, Comparative Study